2012
DOI: 10.1074/jbc.m112.368910
|View full text |Cite
|
Sign up to set email alerts
|

Meprinα Transactivates the Epidermal Growth Factor Receptor (EGFR) via Ligand Shedding, thereby Enhancing Colorectal Cancer Cell Proliferation and Migration

Abstract: Background: EGFR signaling pathway activation is a crucial step in colorectal cancer tumor progression. Results: Meprin␣ sheds the epidermal growth factor ligands EGF and TGF␣. Phosphorylation of EGFR and ERK1/2 is increased and cell proliferation and migration is enhanced after stimulation with meprin␣. Conclusion: Meprin␣ transactivates the EGFR by proteolytic processing of TGF␣ and EGF. Significance: Meprin␣ may be a therapeutic target in colorectal cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 58 publications
4
29
0
Order By: Relevance
“…Besides HCC, there is only limited evidence for a role of meprin α in cell proliferation. A single study has shown that recombinant meprin α could stimulate colorectal cancer cell proliferation via the transactivation of the EGF receptor [11]. In addition, others have shown that the meprin inhibitor actinonin reduced the growth of a large number of tumor cell lines, a finding that we also observed with HCC cells (data not shown).…”
Section: Discussionsupporting
confidence: 77%
“…Besides HCC, there is only limited evidence for a role of meprin α in cell proliferation. A single study has shown that recombinant meprin α could stimulate colorectal cancer cell proliferation via the transactivation of the EGF receptor [11]. In addition, others have shown that the meprin inhibitor actinonin reduced the growth of a large number of tumor cell lines, a finding that we also observed with HCC cells (data not shown).…”
Section: Discussionsupporting
confidence: 77%
“…We identified meprin α as the first soluble metalloprotease that can shed the IL-6R. Interestingly, meprin α was previously shown to cleave and release some ligands of the EGFR17, additionally demonstrating a partially overlapping substrate repertoire with ADAM10/17. On the other hand, meprin β membrane tethering appears to be a prerequisite for IL-6R shedding, because the soluble protease did not result in receptor cleavage.…”
Section: Discussionmentioning
confidence: 94%
“…This cleavage is stimulated by endotoxins (Breshears et al, 2012; Liu Z. et al, 2013) and ROS (Boots et al, 2009) and is mediated primarily by ADAM17 (Peschon et al, 1998), but also by ADAM10 (Hinkle et al, 2003) and MeprinA (Bergin et al, 2008; Minder et al, 2012; Singh and Coffey, 2014). Moreover, TGF-α can interact with and activate EGFR on neighboring cells (Schlessinger and Ullrich, 1992; Thorne and Plowman, 1994; Moral et al, 2001).…”
Section: Tetraspanins and Receptor-mediated Signalingmentioning
confidence: 99%